2022
DOI: 10.3389/fpsyt.2022.893012
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin levels decrease during the treatment of an acute depressive episode

Abstract: ObjectivesOsteocalcin is a protein secreted by osteoblasts with a versatile endocrine role. Several domains in which it plays a role—stress response, monoamine synthesis, and cognitive functioning—are implicated also in the pathophysiology of major depressive disorder. In search of possible objective biomarkers of depression, the aim of the study was to assess the relationship between osteocalcin and depressive symptoms during the treatment of depressive episode.MethodsThe study included female inpatients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…Supporting this hypothesis, lithium use has been associated with decreased osteocalcin levels in bipolar patients compared to the general population while treatment‐naive bipolar patients display higher levels of osteocalcin 14,26 . Osteocalcin seems to be elevated in depressed older adults and decreases significantly after successful treatment of depression 27,28 . We propose that lithium's effects on osteocalcin signaling cascades can explain some of lithium's effects on mood and other stress and age‐related processes including lithium's neuroprotective, osteoprotective, anti‐cancer and anti‐aging properties 5,29–33 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Supporting this hypothesis, lithium use has been associated with decreased osteocalcin levels in bipolar patients compared to the general population while treatment‐naive bipolar patients display higher levels of osteocalcin 14,26 . Osteocalcin seems to be elevated in depressed older adults and decreases significantly after successful treatment of depression 27,28 . We propose that lithium's effects on osteocalcin signaling cascades can explain some of lithium's effects on mood and other stress and age‐related processes including lithium's neuroprotective, osteoprotective, anti‐cancer and anti‐aging properties 5,29–33 .…”
Section: Discussionmentioning
confidence: 77%
“…14,26 Osteocalcin seems to be elevated in depressed older adults and decreases significantly after successful treatment of depression. 27,28 We propose that lithium's effects on osteocalcin signaling cascades can explain some of lithium's effects on mood and other stress and age-related processes including lithium's neuroprotective, osteoprotective, anti-cancer and anti-aging properties. 5,[29][30][31][32][33] Lithium has also been associated with weight gain, which theoretically should be associated with a positive effect on BMD.…”
Section: Discussionmentioning
confidence: 99%
“…OC, a bone-derived protein, is recognized as a marker of bone turnover related to low BMD [ 9 ]. Apart from its impact on bone, the beneficial effects of OC on improving neurological performance were reported, such as cognition impairment, neuromotor dysfunction, and anxiety and depression [ 36 ]. However, there are inconsistent results in the relationship between OC and depressive symptoms, as well as treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study also demonstrated that peripheral OC level was correlated with depressive severity in premenopausal women with major depression, and escitalopram (one of SSRIs) treatment increased serum OC levels [ 37 ], which might be a risk factor of osteoporosis. A recent longitudinal study conducted by Bartecku E et al also enrolled female patients with depression and demonstrated that OC was not related to baseline depressive symptom severity, and pre-treatment OC levels did not predict response to treatment, but the decrease of OC level was associated with the improvements of depressive symptoms after 6 weeks of anti-depressive treatment [ 36 ], suggesting OC may be a candidate biomarker of antidepressant response in female patients. Nevertheless, since most studies on bone health and depression have focused on female patients, no studies have examined the relationship between OC and antidepressant response in male patients with depression.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 9, 2023. ; https://doi.org/10.1101/2023.04.09.536148 doi: bioRxiv preprint osteocalcin (OCN) may modulate GPR158 to alleviate the symptoms of depression, anxiety and memory loss in rodents [55][56][57][58] . OCN can activate the brain-derived neurotrophic factor (BDNF) signaling pathway by connecting GPR158 and RbAp48 in the hippocampus 58,59 .…”
Section: Discussionmentioning
confidence: 99%